2014
DOI: 10.1007/s00787-014-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the mother–child relationship for anxiety disorders and depression: results from a prospective-longitudinal study in adolescents and their mothers

Abstract: This study aims to examine whether (a) low child valence (emotional connectedness) within the mother-child relationship increases the risk for offspring depression, (b) low child potency (individual autonomy) increases the risk for offspring anxiety, and (c) maternal psychopathology pronounces these associations. We used data from a prospective-longitudinal study of adolescents (aged 14-17 at baseline) and their mothers (N = 1,015 mother-child dyads). Anxiety disorders and depression were assessed repeatedly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 76 publications
(134 reference statements)
1
10
1
1
Order By: Relevance
“…The same has been witnessed in a sample of students aged 11to16 going to urban schools in Bangalore [15]. Asselmann and others [16] found that anxious adolescents reported low maternal autonomy support during childhood. Cooper-Vince, Pincus and Comer [17] found that intrusiveness, over involvement and high demandingness from parents were correlated with lack of confidence and lack of coping mechanisms which contributed to anxiety.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The same has been witnessed in a sample of students aged 11to16 going to urban schools in Bangalore [15]. Asselmann and others [16] found that anxious adolescents reported low maternal autonomy support during childhood. Cooper-Vince, Pincus and Comer [17] found that intrusiveness, over involvement and high demandingness from parents were correlated with lack of confidence and lack of coping mechanisms which contributed to anxiety.…”
Section: Introductionsupporting
confidence: 69%
“…Kaushik and Rani [30] have stated that perfectionist attitude of mothers is positively related with anxiety among adolescents. Asselmann and others [16] found that anxious adolescents reported low maternal autonomy support during adolescence. Even though, not much research has focused on direct role of maternal aggression on anxiety among adolescents, but from these studies it can be stated that if mothers are rejecting or aggressive then adolescents are anxious as they spend much of their time with mother at home, thus, aggression from mothers makes them fearful which leads to anxiety.…”
Section: Discussionmentioning
confidence: 94%
“…al., 2015). A combination of antenatal and postnatal maternal 4 depression demonstrates long-term effects on the cognitive development and depressive illness risk of children (Asselmann, Wittchen, Lieb, & Beesdo-Baum, 2015;Sanger, Andrew, & Ramchandani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…al., 2015). A combination of antenatal and postnatal maternal 4 depression demonstrates long-term effects on the cognitive development and depressive illness risk of children (Asselmann, Wittchen, Lieb, & Beesdo-Baum, 2015;Sanger, Andrew, & Ramchandani, 2015).One of the mechanism of transmission of risk for mental health disorders is thought to be associated with the mother's attachment security and her behaviour with the child, and there is growing evidence to suggest maternal attachment style can be seen as a mediator (Toth, Cicchetti, Rogosch, & Sturge-Apple, 2009). However, women with a pre-existing negative model of the self and others have been shown to be at higher risk of developing PND (Wilkinson & Mulcahy, 2010).…”
mentioning
confidence: 99%
“…Further, SCT asserts that individuals' self-efficacy beliefs are influenced by the vicarious experience of socialization agents and that self-efficacy further contributes to an individual's motivation to take action [15]. Given the key role of social relationships and socialization agents according to SCT, it is not surprising that adolescents with positive social relationships with parents, peers, and teachers benefit from these experiences and, therefore, are more likely to display better social, emotional and behavioral outcomes [17][18][19][20][21]. In the present study, we investigate if and how social relationships with key socialization agents (measured as relationships with parents, bullying victimization via peers, and relationships with teachers) are directly associated with adolescents' willingness to intervene in bullying, as well as indirectly through self-efficacy in social conflicts.…”
Section: Introductionmentioning
confidence: 99%